2014
DOI: 10.1371/journal.pone.0085906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sfrp5 on Cytokine Release and Insulin Action in Primary Human Adipocytes and Skeletal Muscle Cells

Abstract: Secreted frizzled-related protein 5 (Sfrp5) is an adipokine with anti-inflammatory and insulin-sensitizing properties in mice. However, the mechanism of Sfrp5 action, especially in humans, is largely unknown. Therefore, cytokine release and insulin signaling were analyzed to investigate the impact of Sfrp5 on inflammation and insulin signaling in primary human adipocytes and skeletal muscle cells (hSkMC). Sfrp5 neither affected interleukin (IL)-6, monocyte chemoattractant protein-1 (MCP-1) and adiponectin rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 22 publications
6
31
0
Order By: Relevance
“…However, our results are in line with a former analysis reporting a positive association between serum Sfrp5 and HOMA-IR in overweight individuals [21]. This would be supported by our mechanistic study using primary human adipocytes which showed an inhibitory role of Sfrp5 on insulin signalling [18]. Furthermore, Sfrp5 decreased insulin-stimulated glucose uptake by 25% in human adipocytes [18].…”
Section: Ngtsupporting
confidence: 92%
“…However, our results are in line with a former analysis reporting a positive association between serum Sfrp5 and HOMA-IR in overweight individuals [21]. This would be supported by our mechanistic study using primary human adipocytes which showed an inhibitory role of Sfrp5 on insulin signalling [18]. Furthermore, Sfrp5 decreased insulin-stimulated glucose uptake by 25% in human adipocytes [18].…”
Section: Ngtsupporting
confidence: 92%
“…Studies focusing on the expression and molecular mechanism of sFRP5 action in cardiac hypertrophy are limited. Carstensen et al [15] demonstrated that sFRP5 reduced IL-6 release from TNF-atreated adipocytes but did not act on hSkMC and suggested that sFRP5 is tissue-specific and dependent on the metabolic and inflammatory state of the target tissue. One study reports that in vivo models of heart failure sFRP 1-4 were expressed in healthy ventricular myocardium, but sFRP3 and sFRP4 increased by 2-3-fold [8].…”
Section: Discussionmentioning
confidence: 99%
“…Among SFRPs, SFRP5 may interact with both canonical and non-canonical WNT signalling pathways , Satoh et al 2008 and might be an import metabolic regulator (Ouchi et al 2010, Mori et al 2012, Carstensen et al 2014. Results from an in vitro study indicated that SFRP5 impairs insulin signalling under normal conditions, but reduces tumour necrosis factor a-induced inflammation in primary human adipocytes (Carstensen et al 2014). In murine mature adipocytes, SFRP5 expression is downregulated in druginduced IR and upregulated by insulin sensitisers (Lv et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…SFRPs prevent downstream WNT signalling by binding to and sequestering WNT ligands in the extracellular space (Bovolenta et al 2008). Among SFRPs, SFRP5 may interact with both canonical and non-canonical WNT signalling pathways , Satoh et al 2008 and might be an import metabolic regulator (Ouchi et al 2010, Mori et al 2012, Carstensen et al 2014. Results from an in vitro study indicated that SFRP5 impairs insulin signalling under normal conditions, but reduces tumour necrosis factor a-induced inflammation in primary human adipocytes (Carstensen et al 2014).…”
mentioning
confidence: 99%